2010
DOI: 10.4314/ajbr.v6i3.54037
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology: A better approach for the early detection of pathophysiologic response to environmental toxicants and disease

Abstract: Our environment is becoming increasingly contaminated by a profusion of substances in the form of industrial and Municipal Waste, air and water pollutants; by heavy metals (such as lead) herbicides, pesticides, cosmetics and so on. The number of chemicals that affect man increases at alarming rates. These agents may be dangerous because they produce biochemical, genetic, structural or physiological lesions in a significant segment of the population. The importance of elucidating the nature and the mechanisms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The concentration of Cadmium across the study area ranged from 0.001 at sampling points B and D to 0.007 at sampling point C. The values recorded were lower than (0.043 mg/l) and (0.072 mg/l) in the water reported by Oguzie and Okhagbuzo [37]. The value of all samples assessed was above the permissible limit of 0.003 ppm set by WHO [24] for drinking water except for sampling points B and D. High concentrations of Cadmium (Cd) have been reported to inhibit the bio-uptake of Phosphorus and Potassium by plants [38].…”
Section: Discussionmentioning
confidence: 66%
“…The concentration of Cadmium across the study area ranged from 0.001 at sampling points B and D to 0.007 at sampling point C. The values recorded were lower than (0.043 mg/l) and (0.072 mg/l) in the water reported by Oguzie and Okhagbuzo [37]. The value of all samples assessed was above the permissible limit of 0.003 ppm set by WHO [24] for drinking water except for sampling points B and D. High concentrations of Cadmium (Cd) have been reported to inhibit the bio-uptake of Phosphorus and Potassium by plants [38].…”
Section: Discussionmentioning
confidence: 66%
“…The authors reiterated further that typhoid fever, amoebic dysentery and cholera are the water related diseases that are commonly reported in Makurdi area. The pollution of River Benue through indiscriminate disposal of industrial and municipal wastewater is not restricted to the city of Makurdi alone, as have reported that the pollution of water bodies has become a momentous global problem these days 7 .…”
Section: Introductionmentioning
confidence: 99%